Functionality of xanthan and almond gum in colloidal shellac nanoparticles containing cinnamon. (October 2019) - Muhammad, D R A; Gupta, V; Doost, A S; Dewettinck, K
Abstract: Instability of shellac nanoparticles at acidic pH is the main challenge of its use as an oral delivery system. This study aims to investigate the functionality of xanthan and almond gum in shellac nanoparticles containing cinnamon prepared by anti-solvent precipitation. The gums were added into the anti-solvent phase while the cinnamon extract was incorporated into the solvent phase. The results show that the minimum concentration of xanthan and almond gum to prevent shellac aggregation at simulated gastric pH (1.2) was 0.3% and 0.6%, respectively. Higher concentration of gums resulted in a bigger particle size and more negative ζ-potential, regardless the type of the gums. Cinnamon loading in the shellac-xanthan gum complex resulted in nanoscale sized particles, while the complex system consisted of shellac, almond gum 0.6% and cinnamon extract created a network entrapping the individual particle. In conclusion, xanthan gum incorporation was better than almond gum to stabilise shellac nanoparticle containing cinnamon in simulated gastric pH. This study confirms that shellac-xanthan gum complex can be potentially used for an oral delivery system of bioactive compounds.